BIODIVERSITY MANAGEMENT AND AGRICULTURAL PRODUCTION: THE GOIAS'S CERRADO - de Oliveira, Eliane; Goulart Duarte, Laura Maria (Science & Technology Journals, 2004)
This article analyses Brazilian savannah (Cerrado) biodiversity management policies and processes in the state of Goiás - Brazil. Some of Cerrado environmental meanings and historical considerations are evaluated considering the land use dynamics, the role of the main actors and the social tensions as they are intrinsically related to the environmental pressure over the biome as a function of time. To help a systemic understanding of the land use dynamics in Goiás's cerrado, the legal and institutional environmental framework is presented along with a discussion of local biodiversity policy.